AN IMPROVED STRUCTURAL MODEL FOR SEISMIC ANALYSIS OF TALL FRAMES (Nigerian Journal of Technology, 2008)
This paper proposed and examined an improved structural model that overcomes the deficiencies of the shear frame model by considering the effects of flexible horizontal members and column axial loads in seismic analysis of multi-storey frames. Matrix displacement method of analysis is used on the basis of the stiffness coefficients of axially-loaded beam element. These stiffness coefficients are obtained as a product of the conventional stiffness coefficients and relevant stability functions which serve as modification factors. The results show that the improved model is more realistic and gives results that are significantly lower than those obtained using the shear frame model.